Evaluation of the antidiarrheal activity of dichloromethane-methanol crude extract of the aerial parts of Croton kinondoensis (Euphorbiaceae) in Mice - Abdullahi Ibrahim Osman Noor; Ermias Mergai Terefe (PLoS ONE, 2025)
Background Diarrhea remains a major global health concern, particularly in developing countries. Resistance to conventional antibiotics underscores the need for effective, plant-based alternatives. Croton kinondoensis, a traditional Kenyan remedy for gastrointestinal ailments, has yet to be scientifically validated. This study assessed its antidiarrheal and antimotility effects in vivo mouse models. Methods Leaf extracts were prepared using dichloromethane/methanol (1:1). Phytochemical screening confirmed the presence of flavonoids, tannins, alkaloids and phenolics. Acute toxicity was assessed via OECD guideline 425. Antidiarrheal activity was tested using a castor oil-induced diarrhea model, and gastrointestinal motility was evaluated using the charcoal meal test. Mice were divided into five groups (n = 6): negative control (distilled water), positive control (loperamide 3 mg/kg), and three test groups receiving C. kinondoensis extract at doses of 100, 200, and 400 mg/kg). Statistical significance was determined using ANOVA and Tukey’s post hoc test to determine significance (p < 0.05). Results The extract showed no toxicity at 2000 mg/kg. In the castor oil-induced diarrhea model, the C. kinondoensis extract at 400 mg/kg inhibited diarrhea by 25.57% (p < 0.05), compared to 71.43% inhibition by loperamide (p < 0.001) e. The charcoal meal transit test, 400 mg/kg of the extract reduced intestinal transit by 27.98% (p < 0.01), compared to 33.43% by loperamide (p < 0.001. Conclusion C. kinondoensis exhibits dose-dependent antidiarrheal and antimotility effects, supporting its traditional use. Although its efficacy was lower than loperamide, the extract demonstrated significant potential as a natural remedy for diarrhea.